Clinical response and pathological changes associated with Corynebacterium pseudotuberculosis infection in mice - Sam Shun, Randolf Paza Tsen; Abdullah, Faez Firdaus Jesse; Saad, Mohd Zamri; Haron, Abd Wahid (2012)
Corynebacterium pseudotuberculosis is a causative agent of caseous lymphadenitis (CLA). Caseous lymphadenitis is a chronic granulomatous infectious disease characterised by the formation of abscesses, typically located in superficial lymph nodes and lungs. Difficulties in early clinical identification of CLA-infected animals have limited the effectiveness of controlling and eradicating this disease. This study was conducted to acquire a better understanding the pathogenesis of CLA through the mice model. Sixteen healthy male mice were divided equally into 2 groups, where the first group of mice were orally inoculated with 1.0 mL of sterile phosphate buffer solution (PBS), pH 7 and the second group of mice were orally inoculated with 1.0 mL of 109 colony forming unit (CFU) of C. pseudotuberculosis. Clinical signs and histopathological changes in visceral organs were compared between the diseased and non-diseased group within the period of 120 hours of post-inoculation. Data was analyzed using the SPSS version 19. This study showed that there were significant (p<0.05) differences in histopathological changes in the lungs, liver and kidneys between diseased and non-diseased mice. Clinical signs were not observed.